1994
DOI: 10.1103/physrevd.50.6939
|View full text |Cite
|
Sign up to set email alerts
|

Exploring lattice quantum chromodynamics by cooling

Abstract: The effect of cooling on a number of observables is calculated in SU(2) lattice gauge theory. The static quark-antiquark potential and spin-dependent interactions are studied, and the topological charge is monitored. The chiral symmetry breaking order parameter χχ and meson correlators are calculated using staggered fermions. Interactions on the distance scale of a few lattice spacings are found to be essentially eliminated by cooling, including the spin-dependent potentials. χχ and meson correlators up to tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…It cannot be used for revealing the full topological structure of the QCD vacuum even if the latter is semi-classical to a certain extent. In particular, it considerably weakens the chiral condensate compared with its value for equilibrium fields [10]. Moreover, it is well-known that the Wilson action depends on the instanton (or caloron) scale-size.…”
Section: Introductionmentioning
confidence: 99%
“…It cannot be used for revealing the full topological structure of the QCD vacuum even if the latter is semi-classical to a certain extent. In particular, it considerably weakens the chiral condensate compared with its value for equilibrium fields [10]. Moreover, it is well-known that the Wilson action depends on the instanton (or caloron) scale-size.…”
Section: Introductionmentioning
confidence: 99%
“…At present we have no explanation for the different behavior observed in the SU (2) and SU(3) calculations. One possibility is that the SU(2) calculation, which was done at β = 2.4, is just deeper in the weak coupling region than the SU(3) calculations done here at β = 5.7 and 5.9.…”
mentioning
confidence: 73%
“…In Ref. [2] it was found that the spin-dependent potential and the chiral symmetry breaking order parameter disappear very quickly upon cooling. In a subsequent nonquenched SU(3) calculation by Edwards et al [3], it was found that cooling has a large effect on the hadron spectrum, tending, for example, to diminish spin-slittings.…”
mentioning
confidence: 99%
See 2 more Smart Citations